Factors influencing the success of franchise industry - Mohd, Zalena; Mohd Ishan, Zahira (Universiti Putra Malaysia Press, 2018)
This paper presents the literature reviews of a study that evaluate and identify the factors influencing the success of franchise industry in Malaysia. The main focused is on the characteristics of franchisor and franchisee that give direct influence to the success of the franchise business. The report can be adopted by the franchisors in determining the best candidate for the business and for franchisee to determine the best franchise business to venture. A systematic review was conducted to explore and to gather the findings from the empirical journal articles. Articles from 2002 to 2016 were included and analyzed. This method gave a thorough understanding of the characteristics that contributed to the success factors from various perspectives. The findings indicates that franchisor internal competencies and franchisee entrepreneurial characteristic had given direct impact towards determining the best criteria for the sales performance and franchisee success. In addition, franchisee management experience is also important for the franchise business success. Result from this study is expected to contribute and to add on to the body of literature on the above subject matter. The author contend that this paper would significantly provide a practical framework for selection process of franchisor and franchisee.